PERAN LITERASI KEUANGAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI SEKTOR INFORMAL - Hasan Husaini (Jurnal Penelitian Ekonomi dan Manajemen (JPEM), 2026)
Financial literacy is the ability of individuals to understand, manage, and make wise financial decisions. This study aims to analyze the role of financial literacy in improving the welfare of people in the informal sector. The research method used is a qualitative approach through a literature review of relevant scientific sources. The findings show that financial literacy plays an important role in improving the welfare of informal sector communities by enhancing their ability to manage income, control expenses, save money, and access formal financial services. Individuals with good financial literacy tend to have higher economic stability and are better able to avoid financial risks. However, challenges such as low education levels, limited access to financial information, and lack of financial education still exist. In conclusion, improving financial literacy is essential to sustainably enhance the welfare of informal sector communities.